2006
DOI: 10.1089/ten.2006.12.2619
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fibroblasts on Tracheal Epithelial Regenerationin vitro

Abstract: Several artificial grafts for covering deficient trachea have been produced through tissue engineering. Recently, our group clinically used an artificial trachea made from collagen sponge for patients with noncircumferential tracheal resection. However, the slowness of epithelial regeneration on the surface of the artificial trachea was confirmed as one particular problem. In this study, we co-cultured tracheal epithelial cells with fibroblasts and examined effects of fibroblasts on epithelial regeneration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 50 publications
(56 reference statements)
3
34
0
1
Order By: Relevance
“…20.21 Indeed, our group has previously shown that stratification, basement membrane reconstruction, apicobasal polarization, and cilia formation of cultured tracheal epithelial cells were promoted by co-culture with fibroblasts. 10 Moreover, following study has indicated that mesenchymal cells stimulate growth and the differentiation of tracheal epithelial cells during tracheal regeneration in a rat tracheal defect model. 22 Thus, mesenchymal cell invasion is an essential event for epithelial regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20.21 Indeed, our group has previously shown that stratification, basement membrane reconstruction, apicobasal polarization, and cilia formation of cultured tracheal epithelial cells were promoted by co-culture with fibroblasts. 10 Moreover, following study has indicated that mesenchymal cells stimulate growth and the differentiation of tracheal epithelial cells during tracheal regeneration in a rat tracheal defect model. 22 Thus, mesenchymal cell invasion is an essential event for epithelial regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…7 To promote regeneration of the tracheal epithelium, our group has studied the effects of fibroblasts, adipose-derived stem cells, and basic-fibroblast growth factor in artificial grafts and shown that they shorten the time for epithelialization and cilia formation. [8][9][10][11][12][13][14] Collagen scaffolds are widely used in regenerative medicine because of their high biocompatibility, but no studies have examined the most suitable structure of collagen scaffold for tracheal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, techniques such as co-culture of two types of cells (i.e. epithelia and fibroblasts) [38] or transplant of the tracheal epithelial cell sheets can be employed to reduce airway stenosis [39]. Overall, for the reconstruction of large segment tracheal defects, the intact epithelial lining is essential to prevent bacterial colonization or infection.…”
Section: Discussionmentioning
confidence: 99%
“…They are able to secrete a variety of growth factors like keratinocyte growth factor, epidermal growth factor, and hepatocyte growth factor [92,93] . The importance of fi broblasts was shown already for epidermal wound healing [93] , oral [94] and corneal epithelial regeneration [95] , and also for tracheal epithelial regeneration [96] . The cocultivation of epithelial cells and tracheal fi broblasts in vitro induced the generation of a layered epithelium containing epithelial cells with cilia, goblet cells, and basal cells.…”
Section: Epithelialization Of Tracheal Scaffoldsmentioning
confidence: 99%
“…The cocultivation of epithelial cells and tracheal fi broblasts in vitro induced the generation of a layered epithelium containing epithelial cells with cilia, goblet cells, and basal cells. Moreover, a basal membrane was constituted in vitro between epithelial cells and fi broblasts where the presence of integrin -β 4 was demonstrated, which is a specifi c marker of basal membranes and of epithelial mucin secretion [96] .…”
Section: Epithelialization Of Tracheal Scaffoldsmentioning
confidence: 99%